Answer:
f(x) = 1/2 times (x − 6)^2 + 3/2
Step-by-step explanation:
The definition of a parabola states that any point of the parabola is at the same distance from the focus and from the directrix. Taking focus at (h, k) and a directrix at y = d:
distance between point (x, y) and the focus = sqrt((x - h)^2 + (y - k)^2)
distance between point (x, y) and the directrix = sqrt((y - d)^2)
Equating them and eliminating the square root:
(x -h)^2 + (y - k)^2 = (y - d)^2
Expanding the y-terms and isolating y
(x -h)^2 + y^2 - 2yk + k^2 = y^2 - 2yd + d^2
(x -h)^2 + k^2 - d^2 = 2y(k - d)
(x -h)^2 + (k - d)(k + d) = 2y(k - d)
(x -h)^2/(2(k - d)) + (k + d)/2 = y
Here h =6, k = 2, d = 1 and y = f(x). Replacing
f(x) = (x -6)^2/(2(2 - 1)) + (2 + 1)/2
f(x) = (x -6)^2/2 + 3/2